Taxation Systems in the EU: The Role of Economic Integration and Global Financial Crisis - Kazim Okan Erol (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This study aims to scrutinize the change of public revenue systems of the EU-15 between 1980 and 2016. The share of consumption taxes in total tax revenues increases and this process have triggered higher tax burden on labor in most of the EU countries via indirect taxation. In this study I use panel data analysis, in order to analyze the impact of global financial crisis on depreciated tax revenues in most of the member states. Political integration and global financial crisis reduce national tax revenues and this revenue loss differs due to tax system asymmetries among member states. Although indirect taxation is an easy way of compensating revenue loss for indebted countries, this type of public finance damages stability of tax revenues in long run.
Keywords: F15; H20; H30; H71; C23; 330; taxation; panel data models; economic integration; fiscal policy